Characterization of trypanosoma congolense stocks from the West and East African regions using molecular karyotyping. - Waihenya, R. (University of Nairobi, 1992)
Trypanosoma congolense, which is responsible for most of animal trypanosomiasis 10 Africa, has a great diversity of variants. Differences occur between stocks from different geographical regions and also between stocks within the same area. In the present work molecular karyotyping was used to investigate the differences between stocks from two geographical regions. Trypanosoma congolense stocks from West Africa (Gambia, Burkina Faso and Nigeria) and East Africa (Kenya and Uganda) were grown and cloned in irradiated mice. The DNA of the derived clones was subjected to Orthogonal Field Alternating Gel Electrophoresis (OF AGE) in order to investigate the genomic relationships amongst the clones. All the clones analysed displayed one overall chromosome pattern resembling that of T. congolense IL Nat. 3.1 (savanna type) established in similar studies. The overall pattern was characterised by the presence of relatively small mini- chromosomes (approx. 50-150kb), lack of medium-sized chromosomes (200-400kb), and a preponderance of large chromosomes (400-750kb). There was no clear-cut distinction between clones from the eastern and the western regions of Africa. Similarities in chromosome profiles were frequently observed between clones from the same stock while distinct variations were noted in the chromosome profiles of clones belonging to different trypanosome stocks. A few clones derived from different trypanosome stocks exhibited similar chromosome patterns. Cross protection experiments, carried out in mice, demonstrated that clones exhibiting similar chromosome profiles conferred protection against each other while those with different profiles did not. Molecular karyo-typing would therefore seem to be a convenient and reliable technique for identifying T. congolense serodemes. The chromosome profiles of the clones were observed to remain stable following chronic infection for four months in goats. The profiles of the chromosome-sized DNA molecules in terms of the number and size also remained stable following transmission through tsetse flies.